Structure and function of the Zika virus full-length NS5 protein - Baoyu Zhao (Nature Portfolio, 2017)
Zika virus infection can cause human birth defects and Guillain-Barré syndrome. Here the authors present the structures of the full-length nonstructural protein 5 and its RNA-dependent RNA polymerase domain of Zika virus, which are targets for inhibitors of virus replication.